The depth of pelagic deposits in the Tethyan Jurassic and the use of corals: an example from the Apennines - Gill, Gabriel A; Santantonio, Massimo; Lathuilière, Bernard (Sedimentary geology, 2004)
Assessing the palaeobathymery of pelagic deposits is rather speculative, as proof through lithology or fossils significant for depth estimates is sparse. This is unfortunate as the bathymetric history of pelagic successions allows to conceive the evolution of continental margins and oceanic basins. Discoveries in coral biology bring an unexpected impact on basin analysis. Evidence strongly suggests that pennular corals, fossil and modern, constitute a zooxanthellate group with an outstanding specialization in colonizing deeper parts of the marine photic zone. This adaptation includes light amplification by autofluorescent pigmented cells, and particular feeding, witnessed by peculiar gastric ducts and skeletal features. Such corals occur in the Umbria–Marche and Sabina Apennines on top of Late Jurassic submarine highs and at basin margins. Values of palaeodepth relative to pelagic deposits are provided by corals and other environmental data. Because depth reconstruction involves classical Tethyan facies, such as Ammonitico Rosso, Aptychus limestone and radiolarian cherts, we must note that these results do not meet with actualistic models relying on carbonate dissolution for estimating depth. Deposits viewed as bathyal to abyssal could also have accumulated within, or just below, the photic zone. Thus, a new insight opens on Mesozoic bathymetries, regarding vast areas (Middle East to Caribbean) and on subjects ranging from platform drowning to regional extension styles.